Minimally Invasive Functional Reconstruction of the Knee - Zhao, Jinzhong; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
The book provides essential surgical techniques to restore knee function, in addition to the anatomical reconstruction. It introduces 44 techniques in separated chapters, which are composized with the same text structure and high-resolution photos. The authors are good at managing and teaching these techniques. The step-by-step descriptions and illustrations are very helpful for the readers of orthopaedic and sports medicine surgeons.
Part 1 Knee Basics -- 1 Arthroscopic Knee Examination -- 2 Treatment Strategies of Meniscus Injuries -- 3 Arthroscopic Meniscus Repair with Autograft Tendon Fibers -- 4 Outside-in Transfer All-inside Meniscus Repair -- 5 Lateral Meniscus Posterior Root Repair -- 6 Combined Pull-out Repair and Centralization for Medial Meniscus Posterior Root Tear -- 7 Arthroscopic synovectomy -- 8 Arthroscopic Treatment of Pigmented Villonodular Synovitis of the Knee -- 9 Hamstring Tendon Harvesting -- 10 Harvesting the Anterior Half of the Peroneus Longus Tendon -- 11 Preparation of Autogenous Tendon -- 12 Graft Length in the Tunnel in Cruciate Ligaments Reconstruction -- Part 2 Anterior cruciate ligament -- 13 Principles of Anterior Cruciate Ligament Reconstruction -- 14 Isometric Single-bundle Transtibial Anterior Cruciate Ligament Reconstruction -- 15 Single-bundle Isometric ACL Reconstruction with Remnant Preservation -- 16 Anatomical Transtibial Single-bundle Anterior Cruciate Ligament Reconstruction -- 17 Treatment Strategies of a Partial ACL Injury -- 18 Single-bundle Anatomical Hardware-free ACL Reconstruction -- 19 Anterior Cruciate Ligament Reconstruction with Internal Bracing -- 20 Anatomical Double-bundle Transtibial Anterior Cruciate Ligament Reconstruction -- 21 Double-bundle Anterior Cruciate Ligament Reconstruction with Remnant Preservation -- 22 Combined ACL-mimicking Anterolateral Structure Reconstruction and Single-bundle Anterior Cruciate Ligament Reconstruction -- 23 Combined ACL-mimicking Anterolateral Structure Reconstruction and Double-bundle Anterior Cruciate Ligament Reconstruction -- 24 Slope-reducing High Tibial Osteotomy and Anterior Cruciate Ligament Reconstruction -- 25 Basic Concepts in Revision Anterior Cruciate Ligament Reconstruction -- 26 Three-in-one Procedure for Revision ACL Reconstruction -- 27 Basic Concepts in the Treatment of Tibial Avulsion Fracture of the Anterior Cruciate Ligament -- 28 Arthroscopic Suture-to-Adjustable Loop Fixation of Adult ACL Tibial Avulsion Fracture -- 29 Arthroscopic Epiphyseal Plate-sparing Fixation of ACL Tibial Avulsion Fracture in Skeletally Immature Patients -- 30 Suture Bridge Fixation for Adolescent ACL Tibial Avulsion Fracture -- Part 3 Posterior Cruciate ligament -- 31 Ultra-Strong Posterior Cruciate Ligament Reconstruction -- 32 Single Bundle Posterior Cruciate Ligament Reconstruction without Remnant Preservation -- 33 Single-bundle Anatomical Posterior Cruciate Ligament Reconstruction with Remnant Preservation -- 34 Lower Tibial Tunnel Placement in Transtibial PCL Reconstruction -- 35 Four-Tunnel Double-Bundle Anatomical Posterior Cruciate Ligament Reconstruction without Remnant Preservation -- 36 Sandwich-Style Posterior Cruciate Ligament Reconstruction: Four-tunnel Double-bundle Posterior Cruciate Ligament Reconstruction with Remnant Preservation -- 37 Basic Concepts in the Treatment of Tibial Avulsion Fracture of the Posterior Cruciate Ligament -- 38 Arthroscopic Suture to Loop Fixation of PCL Tibial Avulsion Fracture -- Part 4 Collateral and Multi ligaments -- 39 The Basic Concept in Treatment of Injuries of the Posteromedial Corner of the Knee -- 40 Structural Augmentation of the Posteromedial Corner of the Knee -- 41 Basic Concept in the Treatment of Knee Posterolateral Corner Injury -- 42 Knee Posterolateral Corner Reconstruction with a Single Tendon -- 43 Arthroscopic popliteal tendon reconstruction for type A PLC injury -- 44 The Lateral Gutter Drive-thru Sign and Drive-thru Test -- 45 Basic Concepts in the Treatment of Knee Dislocation -- 46 Treatment Strategies for Multi Ligament Injuries of the knee -- 47 Simultaneous anterior cruciate ligament, posterior cruciate ligament, posteromedial corner, and posterolateral corner reconstruction of the knee -- Part 5 Patellofemoral Joint -- 48 Basic Concepts in the Diagnosis and Treatment of Patella Instability and Dislocation -- 49 Wide-patellar Insertion Medial Patellofemoral Ligament Reconstruction with Internal Bracing -- 50 Polyethylene Suture Augmentation of the Medial Patellofemoral Ligament in Skeletally Immature Patients with Recurrent Patella Dislocation -- 51 Arthroscopic Release of the Lateral Retinaculum of the Patella -- 52 Tibial Tubercle Transfer: Indications and Modified Fulkerson Osteotomy -- 53 Surgical treatment of Habitual patellar dislocation with patella Baja -- 54 Derotational Distal Femoral Osteotomy For Recurrent Patellar Dislocation -- 55 Biplanar Knee Derotation Osteotomy in the Treatment of Patella Instability -- 56 Rebalance of the Quadriceps Femoris -- 57 Arthroscopic Patellofemoral Arthroplasty for Isolated Patellofemoral Osteoarthritis -- Section 6 Knee Osteoarthritis and Stiffness -- 58 Arthroscopic Arthroplasty for Knee Osteoarthritis -- 59 Anterior Proximal-to-Posterior Distal Oblique Proximal Tibial Osteotomy -- 60 Basic Concepts in the Treatment of Knee Stiffness -- 61 Arthroscopic Release of Severe Flexion- and Extension-impeding Knee Stiffness with Inaccessible Joint -- 62 Zhao Mini-invasive Quadriceps Plasty.
Keywords: Orthopedics; Orthopaedics; Knee -- surgery; Endoscopy